Enabling Decentralized Privacy Preserving Data Processing in Sensor Networks - Hrovatin, Niki (Informatica, 2024)
The paper summarizes the findings of the Doctoral Thesis [1]. We propose a paradigm shift from traditional privacy-preserving joint computation, which relies on data obfuscation methods, to privacy preservation through anonymity. The main contribution of the thesis is a privacy-preserving protocol based on the Onion Routing concept that allows sensor network nodes to jointly compute an arbitrary function and keeps the participating nodes and their inputs private. We demonstrate the protocol's security and, through simulations, its effectiveness in large sensor networks.